Digital filters : principles and applications with MATLAB - Taylor, Fred J., 1940-; IEEE Xplore (Online Service); John Wiley & Sons (Hoboken, New Jersey : Wiley-IEEE Press, 2012)
Solution implementations for digital filter design and analysis using MATLABA professional engineer charged with designing digital filters for sophisticated electronic devices needs more than design theory to get the job done. It is also essential to have practical guidance in how to characterize a digital filter, choose among a vast number of filter design options available in MATLAB and other software, make proper design choices, and enhance a computer-generated design into the optimal filter for a target application. In addition, it is important to develop skills that make it possible to take full advantage of MATLAB's implementation support.Digital Filters delivers both the theoretical and practical knowledge needed to design, implement, and analyze digital filters using MATLAB. It covers:. Sampling, data acquisition, data conversion and quantization, and transforms. Finite impulse response (FIR) filter attributes, types, special cases, and implementation. Infinite impulse response (IIR) filter attributes, types, special cases, and implementation. State variables as an IIR architectural description language. Multi-rate digital filter systems properties and case studiesEach topic in Digital Filters is supported with numerous examples, many involving the use of MATLAB. The MATLAB scripts used to generate these examples and graphics are available from an accompanying website. These scripts can be easily copied and pasted into MATLAB's Command Window and re-parameterized to reflect specific digital filter applications and needs.
PREFACE ix -- CHAPTER 1 INTRODUCTION TO DIGITAL SIGNAL PROCESSING 1 -- CHAPTER 2 SAMPLING THEOREM 11 -- CHAPTER 3 ALIASING 21 -- CHAPTER 4 DATA CONVERSION AND QUANTIZATION 29 -- CHAPTER 5 THE Z-TRANSFORM 41 -- CHAPTER 6 FINITE IMPULSE RESPONSE FILTERS 53 -- CHAPTER 7 WINDOW DESIGN METHOD 71 -- CHAPTER 8 LMS DESIGN METHOD 83 -- CHAPTER 9 EQUIRIPPLE DESIGN METHOD 95 -- CHAPTER 10 FIR: SPECIAL CASES 113 -- CHAPTER 11 FIR IMPLEMENTATION 127 -- CHAPTER 12 CLASSIC FILTER DESIGN 151 -- CHAPTER 13 IIR DESIGN 167 -- CHAPTER 14 STATE VARIABLE FILTER MODELS 183 -- CHAPTER 15 DIGITAL FILTER ARCHITECTURE 197 -- CHAPTER 16 FIXED-POINT EFFECTS 215 -- CHAPTER 17 IIR ARCHITECTURE ANALYSIS 231 -- CHAPTER 18 INTRODUCTION TO MULTIRATE SYSTEMS 249 -- CHAPTER 19 MULTIRATE FILTERS 263 -- BIBLIOGRAPHY 279 -- APPENDIX 281 -- GLOSSARY 287 -- INDEX 295
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: MATLAB; Electric filters, Digital; Signal processing -- Digital techniques -- Mathematics; Electronic books